Kestabilan Global Endemik Model Epidemi SEIR - Roni Tri Putra; Sukatik - -; Sri Nita -; Yandraini Yunida - (Jurnal Ilmiah Poli Rekayasa, 2014)
In this paper, it will be studied global stability endemic of equilibrium points of  a SEIR model with infectious force in latent, infected and immune period. From the model it will be found investigated the existence and its stability of points its equilibrium. The global stability of equilibrium points is depending on the value of the basic reproduction number  If   there is a unique endemic equilibrium which is globally asymptotically stable.